LEGAL CONSEQUENCES OF SPECIAL TAX REGIMES FOR INDIVIDUAL ENTREPRENEURS IN POST-TRANSITION ECONOMIES - Tiutiuriukov, Vladimir (Pravni zapisi, 2024)
This paper provides a comparative legal analysis of the practice of four post-transition economies (Czechia, Kazakhstan, Russia, and Serbia) with special tax regimes for individual entrepreneurs from 1990s till now. We analyze the eligibility criteria and main elements of each special tax regime – whether based on lumpsum tax, on taxation of imputed income, or on taxation of actual income – on a country-by-country basis, for both existing and abolished regimes. The legal implications are also explored. In the conclusion, the paper compares and contrasts their features to identify the advantages (such as consistency of tax system, decrease in compliance burden, automatic adjustment for inflation) and deficiencies (taxpayer uncertainty, susceptibility to abuse of law and tax avoidance).